ELECTRONIC ADVOCACY IN POLICY PRACTICE: A FRAMEWORK FOR TEACHING TECHNOLOGICALLY BASED PRACTICE. - Fitzgerald, Edward; McNutt, John (Journal of Social Work Education)
The 1990s have not been easy times for social welfare advocates and their clients. Not only must advocacy efforts contend with repressive new legislation, but the creation of a new, diffuse policy environment makes many traditional advocacy techniques either ineffective or difficult to use. This article examines the forces that confront today's advocate, suggests ways to address these issues with new technologically based advocacy techniques, and suggests ways to incorporate these techniques into the social welfare policy curriculum. Techniques discussed include database applications, e-mail, Internet publishing, and Internet-based research.